Literacy, Bêtise, and the Production of Species Difference in Ray Bradbury's Fahrenheit 451. Issue 1 (April 2018) - McCorry, Seán
Abstract : Postwar literature (and postwar sf in particular) is marked by a concern that emerging techno-cultural developments would undermine the sovereignty of the humanist subject. The mass production of culture and an increasing dependency on technologies were seen as inimical to individualism, literary culture, and human agency. In the same period, new research into the cognitive and behavioral capacities of nonhuman animals put further pressure on the exceptional status of the humanist subject. Drawing on recent work in posthumanist theory and animal studies, I produce a new reading of Ray Bradbury's Fahrenheit 451 (1953) in the light of this twofold crisis of human exceptionalism. I claim that Bradbury's novel typifies a broader tendency in postwar culture to use animal life as a metric by which to gauge the supposed technological attenuation of subjectivity, and I explore how his pessimistic diagnosis of the emergent mass culture discovers a surprising conjuncture of human, animal, and technology in the postwar moment.